(untitled) (Revista de Ciências Agroveterinárias, 2013)
The definition of critical limits of soil density for development of plants is very complex, since it is dependent on the texture and organic matter content. The relative compaction, that is the percentage ratio of the bulk density to the maximum dry density as determined by the Proctor compaction test, has been presented as a parameter capable of standardizing and delimiting these critical limits. The aim of this study is to describe the procedures that have to be used for the implementation of a Proctor compaction test and make available an Excel worksheet that assists in the calculation of water content that the samples to be compacted must reach, besides calculating maximum dry density and optimum moisture content of soil from equation of degree 2 obtained by analytical form from an unbalanced data set.